A Systematic Review of Clinical Practice Guidelines for Infectious and Non-infectious Conjunctivitis. (3rd September 2022) - Chan, Ving Fai; Yong, Ai Chee; Azuara-Blanco, Augusto; Gordon, Iris; Safi, Sare; Lingham, Gareth; Evans, Jennifer; Keel, Stuart
ABSTRACT: Purpose: To systematically review and critically appraise clinical practice guidelines (CPGs) and summarise the recommendations for non-infectious and infectious conjunctivitis Methods: CPGs published on non-infectious and infectious conjunctivitis between 2010 and March 2020 were reviewed, evaluated, and selected using nine items from the Appraisal of Guidelines for Research and Evaluation II tool (4, 7, 8, 10, 12, 13, 15, 22 and 23). CPGs with an average score for items 4, 7, 8, 12, or 22 below 3 and/or a sum of the two researchers' average score for all nine items less than 45 were excluded. Two authors independently extracted and validated the data using standardised forms. Results: Fifteen CPGs from five sources remained for data extraction. CPGs consistently recommended non-pharmacological interventions (artificial tears, cold compress, avoidance or removal of allergens) for non-infectious conjunctivitis and pharmacological interventions (topical anti-histamine, mast-cell stabiliser and dual-acting agent) for allergy types. Observation without treatment was strongly recommended for non-herpetic viral and bacterial infections. Systemic and topical anti-viral was consistently recommended for herpetic viral conjunctivitis, while systemic and topical antibiotics were recommended for chlamydial and gonorrhoeal conjunctivitis. The methods used to assess the level of evidence and the strength of recommendation varied among CPGs. Conclusions: There are a number of high-quality CPGs for non-infectious and infectious conjunctivitis. While there were a number of consistencies in the recommendations provided within these CPGs, several inconsistencies were also identified. Many of which related to the scope of practise of the targeted end-user of the particular guideline.